The very best of world of sport (Kuala Lumpur : Vscape Enterprise [distributor])
For the best part of 25 years, it held hunderds of thousands of people spellbound. It was the world's longest running sports show and its cast became like family and friends to generations. World of sport, the brainchild of Ron Casey, spawned a thousand imitators, but none could quite match its simplicity, its humour or the legend. From the archives of seven sports, Sandy Roberts take us back on a journey that had its beginning back in 1959.
Keywords: Sports films; Sports in motion pictures